2016
DOI: 10.1007/s00520-016-3401-1
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation therapy in the management of chronic oral graft-versus-host disease

Abstract: Oral pain, sensitivity, and dry mouth improved in most patients. These findings suggest PBM therapy may represent an additional approach for management of oral cGVHD, and suggest that controlled studies should be conducted to confirm the efficacy and safety of PBM therapy in oral cGVHD and to determine optimal PBM therapy protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Based upon this, PBM has been utilized for local treatment of oral GVHD in patients with continuing symptoms and signs despite systemic and topical therapies with corticosteroids and other immunosuppressants. Two reports of patients who were treated with PBM showed mucosal lichenoid change; particularly, ulceration and erythema were improved in 3-4 weeks of treatment and oral pain, and dry mouth improved in most patients ( 221 , 222 ). These findings suggest that PBM may represent an additional approach for the management of oral GVHD and suggest that controlled studies should be conducted to confirm the efficacy of PBM therapy in oral GVHD and to determine optimal PBM therapy protocols.…”
Section: Resultsmentioning
confidence: 98%
“…Based upon this, PBM has been utilized for local treatment of oral GVHD in patients with continuing symptoms and signs despite systemic and topical therapies with corticosteroids and other immunosuppressants. Two reports of patients who were treated with PBM showed mucosal lichenoid change; particularly, ulceration and erythema were improved in 3-4 weeks of treatment and oral pain, and dry mouth improved in most patients ( 221 , 222 ). These findings suggest that PBM may represent an additional approach for the management of oral GVHD and suggest that controlled studies should be conducted to confirm the efficacy of PBM therapy in oral GVHD and to determine optimal PBM therapy protocols.…”
Section: Resultsmentioning
confidence: 98%
“…PBM is already part of the official guidelines for the treatment of OM and is routinely used at hematological and oncological clinics [11,12,18]. Clinical studies also support the use of PBM for other toxicities induced by chemotherapy/radiotherapy including lymphedema, radiodermatitis, osteonecrosis of the jaw, and peripheral neuropathy [7,19,20] as well as oral manifestations of chronic graft versus host disease following allogeneic hematopoietic stem cell transplantation [21,22]. However, all previous reports related to treatments performed by the professional medical team at the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Also the potential application of PBM for management of xerostomia, dysgeusia, radiodermatitis, post-RT fibrosis, chronic oral graft-versus-host disease (GVHD), and breast cancer-related lymphedema has been reported. [10][11][12][13][14][15][16][17] The basic principle of supportive care in cancer is to provide effective management of complications of cancer treatment without compromising or inducing negative effects on oncology outcomes; also bearing in mind unwanted and dire consequences such as tumor persistence, new secondary tumors, or recurrence of the primary disease. Various in vitro studies have suggested that PBM may induce accelerated growth in some malignant cell lines and/or development of malignancy in dysplastic cells.…”
Section: Introductionmentioning
confidence: 99%
“…PBM also has beneficial effects in the management of soft tissue necrosis in patients with head and neck cancer (HNC), and therapy‐induced bone necrosis 7‐9 . Also the potential application of PBM for management of xerostomia, dysgeusia, radiodermatitis, post‐RT fibrosis, chronic oral graft‐versus‐host disease (GVHD), and breast cancer‐related lymphedema has been reported 10‐17 …”
Section: Introductionmentioning
confidence: 99%